Pengaruh Permainan dalam Pembelajaran IPAS Terhadap Motivasi Belajar Siswa Kelas 4 SDN Cibungur - Muharam, Agus; Mustikaati, Wina; Fauziah, Adela; Fadila, Intan; Maria, Salsa (FKIP, PGSD, Universitas Slamet Riyadi, 2024)
This research is an observational study of data on students who are less effective in learning which can indicate a lack of motivation and concentration in student learning in participating in various learning activities both inside and outside the classroom. The objectives of this study include (1) testing the relationship between games and science learning outcomes (2) testing the relationship between students' learning motivation and science learning outcomes (3) the relationship between games and learning motivation and also science learning outcomes. The method used is the class action method or Classroom Action Research, which is research conducted in the classroom by planning an action which is then implemented in the form of a class action. Based on the results of the study showed that the presence of the game will provide an increase in students' learning motivation, can eliminate boredom in students, and can increase their enthusiasm for learning. So with a high enthusiasm for learning, students can also be more prepared in receiving various learning materials that will be delivered.